Modul Pembelajaran Multimedia Interaktif Berbasis Adobe Director Pada Mata Pelajaran Sistem Operasi Sekolah Menengah Kejuruan - Rini Sefriani; Indra Wijaya (INTECOMS: Journal of Information Technology and Computer Science, 2018)
This study aims to design and create interactive multimedia learning modules that meet Valid, Practical and Effective requirements for operating system subjects in Vocational High School. The type of this research is Research and Development research conducted in Vocational High School class X. The population of this study is the students of class X SMK Negeri Batipuh West Sumatra. The sample of this research is students of class X Multimedia SMK N Batipuh West Sumatra. The results of the assessment of the three validators overall validator assessment of the Interactive multimedia learning module amounted to 83.93% so that the validity level can be interpreted Valid is used. Overall assessment of the practicality level of use Interactive multimedia learning module as a learning resource of 89.19%, so the level of practicality can be interpreted Very Practical use. And the effectiveness assessment of Interactive multimedia learning module as a learning resource of 86.90% so that the level of effectiveness can be interpreted Very Effective use. Keywords: Adobe Director, Interactive Multimedia Module, Operating System